Relationship between Growth and Wood properties in Agathis sp. Planted in Indonesia - Futoshi Ishiguri; Kazuko Makino; Imam Wahyudi; Jun Tanabe; Yuya Takashima; Kazuya Iizuka; Shinso Yokota; Nobuo Yoshizawa (Masyarakat Peneliti Kayu Indonesia, 2012)
The present study clarified the relationship between the growth and wood properties of 54-year-old Agathis sp. trees planted in Indonesia. Stem diameter, pilodyn penetration, and stress-wave velocity (SWV) were measured for all trees (35 trees) in a plot (30  30 m) located almost at the center of a stand. Based on the mean stem diameter, 10 standard trees in a plot were selected for measuring the basic density (BD) and compressive strength parallel to grain (CS). Core samples (5 mm in diameter) were collected from the 10 selected trees to determine BD and CS. The mean stem diameter, pilodyn penetration and SWV in the plot were 40.2  11.3 cm, 23.4  2.1 cm, and 3.85  0.43 km/s, respectively. No significant correlation coefficeint (r = -0.327, no significance at 5% level) was obtained between stem diameter and SWV. The mean BD and CS in the 10 trees were 0.42  0.03 g/cm3 and 28.1  2.7 MPa, respectively. A significant positive correlation was observed between BD and CS. Analysis of variance (ANOVA) revealed a significant difference between BD and CS values of the 10 trees, indicating that wood properties may differ among trees with the same standard growth in a stand. From these results, we concluded that wood quality improvement in this species could be achieved by selecting trees with high density and strength in tree breeding programs.